The bacterial pathogen and resistance spectrum in a dermatological inpatient ward: a six-year, retrospective, epidemiological study - Stelzhammer, Philipp; Weber, Wolfgang; Binder, Hermine; Sagel, Ulrich; Aspöck, Christoph; Trautinger, Franz (GMS Hygiene and Infection Control, 2022)
Aim: Treatment of bacterial soft tissue infections is an essential part of clinical dermatology, and the choice of antibiotic therapy is often empirical. The aim of this longitudinal retrospective study was to evaluate bacterial epidemiology, resistance patterns and antibiotic consumption in a dermatological inpatient ward.Method: Bacterial isolates and antimicrobial susceptibility testing from a dermatological inpatient ward were recorded retrospectively from 2011 to 2016. The antibiotic consumption was evaluated and given as the assumed defined daily dose [DDD] per 100 days of covering per year.Results: A total of 4,800 bacterial isolates were included (skin, mucous membrane and wounds 87%, urine 9.5%, blood 1.7%, tissue and tissue fluids 1.6%). The proportion of Gram-positive bacteria was 58% ( 37.8%, 21.5%, . 16.7%). (27.2%), (17.5%) and . (13.1%) were the most common Gram-negative bacteria. The proportion of multi-resistant pathogens was 5.8% for , 0.9%, 0.8% and 1.8% for, and E of all isolates. Beta-lactam antibiotics were the most used drugs (14.4, 10.8, and 9.6 DDD/100 for aminopenicillins, cefalexin, and penicillin G), followed by clindamycin (9.0 DDD/100 patient days). Conclusion: In view of the frequency of bacterial soft tissue infections and their need for inpatient treatment with mostly empirically chosen antibiotics, systematic microbiological surveillance should be recommended for dermatological inpatient wards.